Youthful Intermedia of Aleksander Wat (Anatol Stern and Henryk Berlewi) - Pietrych, Krystyna (Porównania, 2021)
The article discusses Aleksander Wat’s three avant-garde achievements of a visual-linguistic nature, executed together with Anatol Stern and Henryk Berlewi. Interpretation in the transmedia perspective reveals their heterogeneous character, which combines various codes – iconic and verbal. The discussed works make use of an unusual printing layout, employ lettering of various typefaces and diversified graphics, which consequently disrupts the linearity of the plane of the message, offering in its place expressivity and dynamics, requiring from the recipient greater creativity and innovation in the reading of meanings. The typography used in the presented works is not merely a visual addition to the content of the message, but actively modifies and co-creates it.